Species composition and abundance of mosquitoes (Diptera: Culicidae) in a green area surrounded by urbanization in the Neotropical megacity São Paulo, Brazil - Ataide, Livia M. S.; Moura , Carolina A.; Fernandes, Jessica C.; Araújo, Alessandra B.; Izumisawa, Clara M.; Figueiredo, Júlia V. A.; Silva, Raquel E.; Virginio, Flavia (Entomological Communications, 2023)
The urbanization process can influence mosquito biodiversity and abundance, which in turn might affect public health. Here, we investigated mosquitoes’ abundance, diversity and seasonality in an urban green area, located in São Paulo, called Butantan Institute Park. We collected adult mosquitoes for two consecutive years by placing CDC light traps baited with CO2 in three different sites inside the park covering tree strata (canopy, understory and shrub layer). In total, we identified 27,350 mosquitoes belonging to nine different genera and 20 species, including several epidemiological important mosquito species that occupy the urban, sylvatic, and transitional ecotones. The most abundant species were Culex quinquefasciatus (Say, 1823) (Diptera: Culicidae) with 6,892 specimens collected, Culex nigripalpus (Theobald, 1901) (Diptera: Culicidae) with 5,878 and Limatus durhami (Theobald, 1907) (Diptera: Culicidae) with 4,615. While seasonality did not appear to be a strong factor shaping mosquito diversity and abundance, strata had a pronounced effect on the abundance of mosquitoes. The abundance and diversity (Shannon’s index) of mosquitoes was higher at ground level (shrub layer). The high presence of mosquitoes in the park increases the risk of enzootic cycles, re-emergence, or the emergence of new pathogens in the urban environment. For instance, we found one specimen of the genus Sabethes (Robineau-Desvoidy, 1827) indicating that monitoring is very important to prevent yellow fever outbreaks in São Paulo city. Finally, several aspects of mosquito biology and dispersion are discussed in more detail.